(3MjGI GdMjhGf GdcHQis - (3eMeO Hf ehSi Hf YjSi GdOejQj GdTGaYj , ceGd GdOjf CHh GdHbGA,J (B808 (3g` s ((3eMeO Hf eMeO Hf jhSa GdTGaYj s)
(3ChdgG (B:s
(3eHJhQ, hChd GdehLhO efg jHOC HGdcdGe Ydi GdNdO Hbhdg(B: (3hLO NddG aONd ajg MJi bdY GdSO haGV Ydi CehGdge aZQbgG hOaf HjhJge HGdQed haQbhG heRbhG MJi UGQhG eKdG abGdhG JaQbhG CjOj SHG hCjGOj SHG s
(3BNQgG (B:s
(3GdPj GSJNQL Gddg ef dYGHg GdYSd hGdTeY hLYd CMOgeG VjGA hGdBNQ TaGA hGHJOF Hedc GdhMT GdPj efg GdTLGYI oJbJfi hMSHfG Gddg JYGdi hcai hUdi Gddg Ydi SjOfG eMeO GdfHj GdeUWai hYdi Bdg hCUMGHg Cgd GdUOb hGdhaG s
(3GdbSe GdCNjQs
(3Yf fSNI ofbdJ Yf fSNI GdeDdas
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B118 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B65 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B178s
Keywords: (3GdCOHs